Perspectives of young adult males who displayed harmful sexual behaviour during adolescence on motive and treatment. Issue 2 (4th May 2019) - Kjellgren, Cecilia
ABSTRACT: Few studies have examined the subjective experiences of young people following interventions for sexually abusive behaviour. To learn more about how this population experienced these interventions and how these interventions, affect their adult life, 22 adult males (m = 22 years) who were assessed as teenagers (m = 15 years) for sexually abusing children or peers were interviewed, on average six years after the assessment of their offence. Three main themes were identified: something sexual happened (recalling memories of the sexual acts and motives of the behaviour), societal actions (interventions offered), and life has been affected (memories and feelings associated with the abuse still being present). Seven respondents (32%), who all had a cognitive disability, had sexually reoffended by follow-up. If the respondents received interventions that focused on their abusive behaviour, they were likely to find the interventions helpful. Interventions that did not address abusive behaviour, were perceived as less helpful for dealing with their behaviour, and the short- and long-term consequences associated with this behaviour. Respondents reported feelings of sadness and guilt associated with their sexually abusive behaviour and these feelings remained into adulthood. These findings suggest that interventions for this population need to address the individual needs of the adolescent as well as sexual behaviour problems. In addition, interventions should include opportunities for follow-up.